On the transmission time of fountain code based parallel relay network - WU Dan; TIAN Ya-fei; YANG Chen-yang (Tongxin xuebao)
In order to reduce the complexity of transmission protocols and the number of feedback links,fountain code was applied to the multi-stage parallel relay network for open-loop error control.The fountain code based network trans-mission scheme and frame format were presented.The transmission time for both the fountain code based scheme and the conventional ARQ based scheme was analyzed and compared.Results show that the total time consumed under fountain code based scheme can be significantly reduced compared to the ARQ based scheme.With the increase of relay numbers,the advantage of the fountain code based scheme is more evident.